THE DEVELOPMENT OF A HUMANITARIAN APPROACH IN THE REQUEST FOR A WORLD WITHOUT NUCLEAR WEAPONS - Henrique Melchior Nunes da Horta, Pedro (2022)
This article aims to consider the progressive development of a humanitarian approach in thediscussions at multilateral fora in which states and non-governmental organizations started to advocate for the importance of the application of humanitarian perspectives in international treaties. The intention was to reduce human suffering that is caused by wars, with a concept known as Humanitarian Disarmament. In the case of this article, I will work with the nuclear weapons example, a type of weapon that is strategic to states, yet, due to the operation of the so-called Global Civil Society (represented by the non-governmental organization ICAN) it has been prohibited with the 2017 Treaty on the Prohibition of Nuclear Weapons. For this purpose, the article will be divided into two parts, the first focusing on the theoretical underpinnings that allowed the adoption of the treaty and the second being a factual analysis of how this initiative happened in multilateral fora.